Sistem Ekonomi Islam Sebagai Pondasi Ekonomi Masyarakat Melayu Dalam Menghadapi ASEAN Economic Community (AEC) - Muhammad Fadhil Junery (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2015)
Islam besides having fikrah (draft) also has thariqoh (method) how to apply the concepts that already exist. The basic principle of Islamic economic system, namely: the principle of individual freedom, the principle of property rights, the principle of economic inequality within reasonable limits, the principle of social security, Social security principle, the principle of the widespread distribution of wealth, the prohibition to accumulate wealth principle, the principle of the prohibition against anti-social organizations and the principle of the welfare of individuals and society. A major culture shift is needed in developing the local economy. Although the central and local governments have run a populist economic program, the high jump should be made to cross the chasm that separates culture trade farmers and small-scale to sophisticated commercial culture. Initial concrete steps to develop the economy with the concept of community empowerment in facing the ASEAN Economic Community (AEC), namely: First, apply the Islamic economy. Second, community mental preparation. Third, strengthen the potential resources owned or public (empowering).